Participation by 10th - form students in groupwork activities in speaking lessons at Thanh Ha high school, Hai Duong - Dang, Thi Hoa (University of Languages and International Studies, 2017)
This study generally attempts to investigate grade 10 students' participation in groupwork activities in speaking lessons. Students’ preference, their involvement as well as their difficulties in oral group activities were identified. Besides, the potentia (...)